Adaptive fiscal strategies for strengthening local taxing power: Evidence from Jambi Province - Junaidi, Junaidi; Hastuti, Dwi; Ramadhan, Raihan Fajri; Widiastuti, Fitri; Zevaya, Faradina; Siga, Mustaqim; Irawan, Deki (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
The transformation of regional taxation is a strategic agenda aimed at strengthening fiscal capacity, reducing dependence on central government transfers, and supporting sustainable development within the framework of regional autonomy. This study aims to identify the regional tax instruments with the greatest potential, analyze the challenges and opportunities associated with implementing local taxing power, and formulate adaptive fiscal policy strategies in Jambi Province. The research employs a qualitative descriptive-analytical approach, drawing on primary data from in-depth interviews and focus group discussions (FGDs), as well as secondary data from regional budget (APBD) reports, local revenue (PAD) statistics, and regional tax realization for the period 2021–2024. Thematic analysis was conducted using NVivo software, complemented by quantitative data triangulation. The findings reveal that the largest tax potential in Jambi lies in the Street Lighting Tax, Specific Goods and Services Tax, Land and Building Acquisition Duty (BPHTB), and Rural and Urban Land and Building Tax (PBBP2), with varying dominance across districts and municipalities according to their respective economic characteristics. The main implementation challenges include low taxpayer compliance, weak administrative systems and institutional coordination, limited human resources, and disparities in infrastructure development across regions. Nonetheless, significant opportunities exist through the growth of the digital economy, the rise of online-based SMEs, the development of tourism and real estate sectors, and the diversification of resource-based taxation. This study recommends adaptive fiscal strategies built upon three key pillars: regulatory reform, institutional and technological capacity building, and cross-sector collaboration, accompanied by public outreach. Such strategies are expected to foster a more inclusive, transparent, and efficient regional taxation system while strengthening fiscal independence in the post-HKPD 2022 era.